Rhodium-Catalyzed Reaction of 2H-Azirines with Carbonyl-ene-yne Compounds Giving 1-Furyl-2-aza-1,3-dienes - Okamoto, Kazuhiro; Watanabe, Masahito; Mashida, Ayano; Miki, Koji; Ohe, Kouichi (Synlett, 2013)
A rhodium(II)-catalyzed reaction of carbonyl-ene-yne compounds, which are used as furylcarbene precursors, with 2H-azirines gave 1-furyl-2-aza-1,3-dienes as products. We propose that the title compounds are formed by the addition of furylcarbene–rhodium(II) complexes to 2H-azirines followed by opening of 2H-azirine rings.
Keywords: alkynes; rhodium; carbenes; azirines; ring-opening reaction